KOMPARASI KETAHANAN BANK SYARIAH DAN BANK KONVENSIONAL SELAMA PANDEMI COVID-19: ANALISIS INDEX BANKING CRISIS - Anisa Cindy Arzamitha; Munawar Ismail (Islamic Economics and finance in Focus, 2024)
This study aims to compare the resilience of Islamic and conventional banking during the COVID-19 pandemic. Banking resilience is measured by the Banking Crisis Index (IBC) which is compiled using five components, namely Non Performing Loan (NPL)/Non Permorming Financing (NPL), Loan to Deposit Ratio (LDR)/ Financing to Deposit Ratio (FDR), Biaya Operasi Pendapatan Operasi (BOPO),  Capital Adequacy Ratio (CAR), dan Return on Assets   (ROA). The data used was obtained from monthly reports on Indonesian banking statistics from 2020-2022 which were then analyzed using a Mann Whitney U-Test. The result of this study indicate that there are significant differences in the resilience of islamic and conventional banking during COVID-19 with a significance value of 0,000>0,05.